The effect of movies on listening comprehension for Saudi EFL students - Alqahtani, Samah Abdullah; Alhamami, Munassir (Englisia Journal, 2024)
This study investigated the effectiveness of using movies to improve the listening skills of Saudi EFL students and their attitudes towards movie-based activities. A questionnaire was administered to 147 participants, 113 of whom were female and 34 of whom were male. The participants were divided into four age groups: 18-20 years, 21-25 years, 26-30 years, and above 30 years. Participants were required to have no history of hearing impairment or learning disabilities that may affect listening skills. Descriptive and inferential statistics were used to analyze the data. The results showed that movies had a positive impact on students' listening skills, and most participants had a positive attitude towards using movies as a learning tool. However, some challenges were also identified, such as finding appropriate movies and lacking guidance on effective movie use. The findings of this study have implications for English language teachers, providing insights into the benefits and challenges of using movies, and suggesting the need for training programs on incorporating movies into language teaching. Overall, this study contributes to understanding how technology-based tools like movies can enhance language learning outcomes.